Análisis comparativo de los activos biológicos y su relación con los estados financieros de la avícola Cecilita del cantón Pelileo, período 2019 - Luis Fernando, López Quishpe (2021)
ABSTRACT International Accounting Standard 41 establishes the accounting treatment of biological assets throughout their biological transformation process, i.e., growth, degradation, production and procreation. It also requires the valuation of these biological assets at fair value less estimated costs up to the point of sale. If the fair value cannot be reliably determined, it requires that they be valued on the basis of cost less accumulated depreciation or impairment losses. The present research work aims to value biological assets based on IAS 41 and compare it with the valuation performed by the poultry company. The development of the research began with the statement of the problem to establish the objectives. In the methodological framework, the deductive method was applied to consider the information of the standard, the type of research used was documentary and field, to obtain the necessary information for its development, the research design was non-experimental, as the variables of the study were not manipulated, the approach was qualitative and quantitative to consider basic criteria of the standard and perform numerical calculations, the level of research was descriptive because it allowed us to know the current situation of the poultry farm with the support of an interview that was applied to the farm accountant. As a result of the research, it was observed that the biological assets account is undervalued, preventing from reflecting the real financial information in the poultry farm's financial statements. Key words: Valuation, Biological assets, Active market, Depreciation. Replacement value, Discard value. Undervalued, Overvalued. Cost model. Reviewed by: MsC. Edison Damian Escudero ENGLISH PROFESSOR C.C.0601890593